Moving purchasing & supply management beyond a cost-focused identity. Issue 3 (June 2021) - Ueltschy Murfield, Monique L.; Ellram, Lisa M.; Giunipero, Larry C.
Abstract: Practitioners and researchers recognize that purchasing and supply management (PSM) contributes value to business performance beyond reported cost reductions, though capturing and evaluating such contributions is often challenging. The goal of this research is to understand roadblocks impeding the recognition of PSM's contributions beyond cost reduction, and suggest potential solutions to these challenges. Social identity theory offers a conceptual framework to study PSM's self-identity and how it is perceived by others in the organization. Gaining acceptance for value-added metrics is critical to move perceptions of PSM's contribution beyond cost reduction and achieve its full potential. Social identity theory is used as a lens to assess the data and develop propositions. Using a qualitative interview method, the researchers identified important roadblocks hindering PSM's attainment of a broader value-based perception. PSM's identity is closely linked to cost-savings by itself, other functions and upper management. These perceptions are further reinforced by PSM through excessive cost reporting metrics. We provide two suggested solutions for PSM to expand its recognition beyond cost savings: 1) PSM must change its narrative and associated self-identity; and 2) PSM needs to develop metrics that are meaningful across multiple areas of the business. Highlights: PSM contributes broadly to organizational success, but is still primarily linked to cost savings. PSM's group identity, social identity and self-identity linked to cost-savings create roadblocks. PSM must change its narrative and associated self-identity to move beyond cost. Linking PSM with established business value metrics is critical for PSM's identity shift.